A Study on the Problems of Learning Experiences Management of Early Childhood Teachers in Xiyuehe Kindergarten - ์Nakunsong Thatsanee; Lihua, Liu (Interdisciplinary Academic and Research Journal, 2024)
Background and Aims: Early childhood education is an important level of education for educational organizers and related parties. Especially mentors, teachers, or child caretakers who play a huge role in cultivating character traits in children by organizing various activities to prepare and lead children to develop physically, socially, emotionally, and intellectually. Thus, this paper aims to (1) study the problem of organizing learning experiences for early childhood teachers in Xiyuehe Kindergarten. (2) study the learning experiences of early childhood teachers in Xiyuehe Kindergarten. Methodology: The target group used in the research is 16 early childhood teachers in Xiyuehe Kindergarten, Suzhou, China, in the second semester of the academic year 2023, obtained from specific selection. The tool used to collect data was a questionnaire on organizing learning experiences for early childhood teachers, consisting of 3 sections. Content validity was between 0.80 - 1.00. Statistics used for data analysis included mean, and standard deviation. Results: The research results found that (1) Problems in organizing learning experiences for early childhood teachers at Xiyuehe Kindergarten School were found to be at a high level overall when sorted from highest to lowest as follows: in terms of preparing the school curriculum in terms of organizing learning experiences and developmental evaluation. (2) Current situation in organizing learning experiences for early childhood teachers Xiyuehe Kindergarten School, from 5 questions, found that early childhood teachers have a (2.1) understanding of organizing learning experiences. Most understand organizing learning experiences through play, exploration, and hands-on activities. Child-centered Organize learning experiences according to each child’s interests, needs, and abilities. Provide a structured but flexible environment. Emphasis on holistic child development. (2.2) The most important task in organizing learning experiences. It was found that teachers emphasized the importance of a holistic approach to child development. By considering the development of diverse children. Children will receive development in all 4 areas according to their age and individual abilities. Need to be supported by Help from parents, caregivers, teachers, and other related personnel. (2.3) Your relationship with the children in your class It has been. It was found that early childhood teachers place importance on promoting strong relationships with students by creating a supportive environment. Aims to understand the needs of each child. Focus on developing good relationships with children. In addition to focusing on academics By giving importance to the potential of each child. At the same time, we aim to be a good mentor and role model for children. (2.4) The most important questions to ask students when organizing learning experiences. It was found that early childhood teachers emphasized asking questions that promoted skills. Effective open-ended questions Promote creativity critical thinking and problem-solving Allow children to connect learning with real experiences. Questions that stimulate curiosity. (2.5) Questions that stimulate curiosity Opinions about organizing learning experiences in schools It was found that kindergarten teachers used a variety of teaching methods. with an emphasis on interactive play Promoting creativity and giving children direct experience for holistic child development Focus on social and emotional learning through play and natural integration. Use storytelling activities, music, and daily routines. Give children individual attention There is integration of technology. Promote a safe parenting environment Create a balance between child-initiated and teacher-initiated activities. and attach importance to family participation. Conclusion: The results highlight both the challenges and strengths in organizing learning experiences for early childhood teachers at Xiyuehe Kindergarten School. Despite organizational hurdles, teachers demonstrate a deep commitment to fostering holistic development, nurturing relationships, and promoting creativity and critical thinking in their students. Addressing the identified challenges while harnessing these strengths through collaborative efforts will be key to further enhancing the quality of early childhood education at the school.